From stakeholders to communities of care - Checchi, Marco; Kokkinidis, George (My University, 2024)
This chapter focuses on two case studies in Greece and the UK to show the necessity to rethink the idea of stakeholders in organizational settings that explicitly aim to be radically transformative. Alternative organizations, like those discussed in this chapter, reconfigure distinct and potentially conflicting interests from a perspective of care that transforms the practices and the subjectivities at stake within and around organizations. The idea of care and caring is central to our analysis, and we look at it not as a private affair or an ethical matter, but as a central organizational principle that is fundamentally collective and political. We draw on data collected through a range of qualitative methodologies to explore the repoliticization of care and the reconfiguring of stakeholders into careholders by looking at alternative practices of organizing where different stakeholders within and outside the organization deliberately engage with the underlying and structural power relations that define their relevant positionalities. We illustrate how the overcoming of a traditional stakeholders' approach passes through the emerging of an alternative diagram of power, a set of affective relations reconfigured through performative intra-actions between the members of these communities, their discourses, their practices, the multiple materialities that constitute these spaces.